Is it really Smart Growth? - Reynolds, Larry J. (Kansas State University, 2009)
A study was performed comparing the results of two different Smart Growth Scorecards against a land development project, Southlake Town Square, which the Smart Growth Network claims to be Smart Growth. Southlake Town Square was chosen from a list of projects published by the Smart Growth Network entitled “This Is Smart Growth: A List of Featured Communities”. The purpose of this study was to determine if Smart Growth Scorecards support what the Smart Growth Network claims to be Smart Growth. The Ten Principles of Smart Growth, published by the Smart Growth Network, served as a measurable set of definitions which cumulatively define Smart Growth. The New Jersey Smart Growth Scorecard for Proposed Developments published by New Jersey Future and the Austin, Texas Smart Growth Criteria Matrix by the City of Austin Transportation, Planning and Design Department were selected from the U.S. Environmental Protection Agency (E.P.A.) website on Smart Growth. This investigation revealed that the two scorecards yielded similar results suggesting that Southlake Town Square failed to score better than 60% of the total possible points on either scorecard. Southlake Town Square failed to produce convincing results when the scorecards were analyzed in terms of the Ten Principles of Smart Growth. Furthermore, significant differences were observed in the measuring techniques of both Smart Growth Scorecards. The results of this study sufficiently conclude that significant inconsistencies exist between what the Smart Growth Network claims to be Smart Growth and what currently available Smart Growth measuring tools, Smart Growth Scorecards, say about a Smart Growth project. Consequently, the contemporary movement called Smart Growth maybe drastically weakened by unsupported claims, a lack of consistent, standardized measuring techniques, and differing definitions of Smart Growth.
Keywords: Smart Growth; Southlake Town Square; Urban Planning; Land Development; Land use; Smart Growth Network; Architecture (0729); Landscape Architecture (0390); Urban and Regional Planning (0999)